Enhancing Science Learning through Science Trade Book Reading for 5th Graders - Ching-San Lai; Kuei-Lin Chan (Seyit Ahmet Kıray, 2020)
This study explores the learning outcome of science learning with integrating science trade book reading of 5th graders. A quasi-experimental design was used in this study at an elementary school in New Taipei City. Students in the experimental group (N=59) were given instructional strategies on integrating science trade book reading into science learning, while the control group (N=59) received traditional instruction. Three science trade books were used in science reading strategies for the experimental group. Two research instruments were used in this study were a science achievement test (30 items, KR21=.80), and an attitudes toward science scale (31 items, Cronbach α=.94). The results were processed by ANCOVA analysis, finding that students in the experimental group got higher scores than students in the control group (F= 4.921, p < .05). Although there was no significant difference between the two groups in the outcome of the attitudes toward science scale, feedback from students in the experimental group showed that they enjoyed and benefited from integrating science trade book reading into science learning and hoped can they could continue to learn more science by integrating science trade book reading. Thus integrating science trade book reading into science learning was beneficial for the 5th graders in this study.